An innovative sliding mode load controller for gas turbine power generators: Design and experimental validation via real-time simulation. (15th February 2021) - Palmieri, A.; Lanzarotto, D.; Cacciacarne, S.; Torre, I.; Bonfiglio, A.
Abstract: This paper deals with the design of an innovative load controller for heavy-duty gas turbine (GT) power generators and with its practical implementation on real industrial power plants. A robust controller based on the Sliding Mode control technique is designed, in order to improve the performance of the GT system with respect to the traditional Proportional-Integral-Derivative regulation. The main aim of this paper is to fill the gap between theoretical studies and the real deployment of the advanced GT controller based on the Adaptive Sliding Mode control, an improved variant of the traditional Sliding Mode. The main focus of this work is to solve the main limitations of previous works for an effective deployment of the proposed controller on real industrial devices. This work is developed in collaboration with Ansaldo Energia S.p.A., the interaction with the industrial partner is one of the key points of this paper allowing the implementation of the proposed controller on real industrial microprocessors and the validation in a Real Time Simulation environment at the Ansaldo Energia S.p.A. R&D laboratories. The controller validation, performed in a Hardware-In-the-Loop set-up, showed highly satisfactory results and important improvements in comparison with the traditional regulation of the GT power generator. Highlights: Adaptive Sliding Mode control for gas turbine power Generators. Increasing the tradition power plant performance to host RES. Controller design adaptation for the implementation on a rea industrial controller. Validation of the proposed controller in a real gas turbine power generator architecture. Experimental validation on a high-fidelity Real-Time Model in a Hardware in the Loop set-up.